SEJARAH ISLAM PADA MASA DINASTI SYAFAWI DI PERSIA - Harisseptian Harisseptian; Afrizal Afrizal; Syawaludin Syawaludin (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The Safavid kingdom originated from a Tarekat movement that was founded in Ardabil city in Azerbaijan. Before becoming a kingdom, the Safavids experience two phases of growth. The first phase of this dynasty was active in the religious field and the second as a political movement. In the history of the Safawi journey, progress has been achieved in various fields, including politics, economics, science and culture, military. In the early days, the Safavid kingdom was in the form of a theocratic government, the highest state officials were held by the shah's representatives, both in political and religious matters. The purpose of this article is to find out the history of the Safavid dynasty in Persia. The method used in this writing is a literature review, while the results of the panel research are: In other literature, Badri Yatim explains that the cause of the decline and destruction of the Safavid kingdom was the Shiite Safavid Kingdom was a direct threat to its territory. The conflict between the two kingdoms lasted a long time, although it stopped briefly when peace was achieved during the time of Shah Abbas I.